The Role of Character Education, Creativity, Motivation, and Social Media Use as Predictors of Junior High School Academic Achievement - Sidqi, Moch. Hasan; Darmawan, Didit (Jurnal Pendidikan Progresif, 2025)
The Role of Character Education, Creativity, Motivation, and Social Media Use as Predictors of Junior High School Academic Achievement. Objectives: The importance of this study is to fill the gap of previous research that rarely analyzes the influence of character education, academic creativity, academic motivation and social media on academic achievement by taking all junior secondary students without distinguishing certain classes and subjects. Therefore, this study aims to determine and analyze the influence of all independent variables on academic achievement. Methods: The study was a quantitative survey with a population of 115 students. The sample was taken from the population using the total sampling technique, so the sample amounted to 115 students. The data analysis technique used multiple linear regression (t-test, F- test, and coefficient determination) which was previously tested for data quality (Corrected Item- Total Correlation validity test and reliability test) and classical assumption test (Probability plot test, multicollinearity test, autocorrelation test, and scatter plot heteroscedasticity. Findings: This research shows that all the independent variables of the study (Character education, academic creativity, academic motivation, and social media) positively influenced students' academic achievement, both partial and simultaneous analysis. Conclusion: Based on the research results, all hypotheses were accepted, namely character education has an effect on academic achievement (H1), academic creativity has an effect on academic achievement (H2), academic motivation has an effect on academic achievement (H3), and social media has an effect on academic achievement (H4). MTs Bi'rul Ulum Gedangan Sidoarjo can implement the implications for paying attention to academic achievement by ensuring the implementation of policies for integrating character education values runs effectively, increasing adequate and stable resources and infrastructure, and creating stimulus by channeling social media content related to subject matter. Future research can carry out research that focuses on all the variables of the current study, but uses Alpha Generation subjects. Keywords: character education, academic creativity, academic motivation, social media, academic achievement.